2013
DOI: 10.1016/j.bbabio.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase assembly

Abstract: Nitrogenase contains two unique metalloclusters: the P-cluster and the M-cluster. The assembly processes of P- and M-clusters are arguably the most complicated processes in bioinorganic chemistry. There is considerable interest in decoding the biosynthetic mechanisms of the P- and M-clusters, because these clusters are not only biologically important, but also chemically unprecedented. Understanding the assembly mechanisms of these unique metalloclusters is crucial for understanding the structure-function rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 59 publications
(82 reference statements)
0
51
0
Order By: Relevance
“…[9] for a review), different overall nitrogen-catalyzed reactions are found in textbooks. The following is a discussion on the pitfalls that may cause such discrepancies.…”
Section: The Nitrogenase-catalyzed Reactionmentioning
confidence: 99%
“…[9] for a review), different overall nitrogen-catalyzed reactions are found in textbooks. The following is a discussion on the pitfalls that may cause such discrepancies.…”
Section: The Nitrogenase-catalyzed Reactionmentioning
confidence: 99%
“…In this minireview, we describe a model for mammalian cobalamin trafficking, which includes strategies for conversion of inactive precursors to the active cofactor forms methylcobalamin (MeCbl) 3 and 5Ј-deoxyadenosylcobalamin (AdoCbl; coenzyme B 12 ) and discuss the human diseases that result from impairments along the trafficking highway. We posit that the navigation strategy for B 12 , in which a rare, reactive, and high value cofactor is sequestered and targeted to client proteins, might represent a general archetype for the trafficking of other essential but scarce organic and organometallic cofactors.…”
mentioning
confidence: 99%
“…Similarly, elaboration of metals into clusters often occurs on chaperones that subsequently transfer the cofactor to target proteins. The interprotein transfer of metals can occur via ligand exchange reactions that are driven by differences in metal coordination geometry and affinity between the donor and acceptor proteins (2,3). Seclusion of cofactors in chaperones during assembly/processing into their active forms minimizes unwanted side reactions, whereas guided delivery averts dilution and promotes specificity of cofactor docking.…”
mentioning
confidence: 99%
“…How metalloenzymes mature has been investigated for some systems, revealing surprisingly complex maturation pathways (2)(3)(4)(5)(6)(7)(8). Enzymes containing nickel, although still relatively small in number, play critical roles in archaea, bacteria, and eukarya, through which they impact the global hydrogen (Ni,Fe-hydrogenase), nitrogen (urease), and carbon (acetylCoA synthase, carbon monoxide dehydrogenase, and methylCoM reductase) cycles (9).…”
mentioning
confidence: 99%